The role of 99mTc-HMPAO-labelled white blood cell scintigraphy in the diagnosis of cardiac device-related infective endocarditis. (12th October 2019) - Holcman, Katarzyna; Małecka, Barbara; Rubiś, Paweł; Ząbek, Andrzej; Szot, Wojciech; Boczar, Krzysztof; Leśniak-Sobelga, Agata; Hlawaty, Marta; Wiśniowska-Śmiałek, Sylwia; Stępień, Agnieszka; Podolec, Piotr; Kostkiewicz, Magdalena
Abstract: Aims: The hybrid technique of single-photon emission tomography and computed tomography with technetium99m-hexamethylpropyleneamine oxime–labelled leucocytes (99mTc-HMPAO-SPECT/CT) is an emerging diagnostic technique in patients with cardiac device-related infective endocarditis (CDRIE). This prospective study assessed the 99mTc-HMPAO-SPECT/CT diagnostic profile and its added value to the modified Duke criteria (mDuke) in CDRIE diagnostic work-up. Methods and results: The study examined 103 consecutive patients with suspected CDRIE, who underwent 99mTc-HMPAO-SPECT/CT. Diagnostic accuracy was calculated based on a final clinical CDRIE diagnosis, including microbiology, echocardiography, and a 6-month follow-up. Subsequently, we compared the diagnostic value of the initial mDuke classification with a classification including 99mTc-HMPAO-SPECT/CT positive results as an additional major CDRIE criterion: mDuke-SPECT/CT. Overall, CDRIE was diagnosed in 31 (31%) patients, whereas 35 (34%) 99mTc-HMPAO-SPECT/CT were positive. 99mTc-HMPAO-SPECT/CT was characterized by 86% accuracy, 0.69 Cohen's kappa coefficient, 84% sensitivity, 88% specificity, 93% negative, and 74% positive predictive values. The original mDuke displayed 83% accuracy, 0.52 kappa, whereas mDuke-SPECT/CT had 88% accuracy, and 0.73 kappa. Compared with mDuke, mDuke-SPECT/CT showed significantly higher sensitivity (87% vs. 48%, P  < 0.001). According to mDuke, 49.5% of patients had possible CDRIE, and after reclassification, that figure dropped to 37%. Furthermore, having assessed the diagnosis categorization improvement following the incorporation of 99mTc-HMPAO-SPECT/CT, the net reclassification index value was found to be 31.4%. Conclusion: In patients with CDRIE, 99mTc-HMPAO-SPECT/CT provides high diagnostic accuracy, whereas a negative scan excludes CDRIE with high probability. Inclusion of 99mTc-HMPAO-SPECT/CT into mDuke diagnostic criteria yields significantly higher sensitivity and a reduction in possible CDRIE diagnoses.